IMPLEMENTASI MEDIA APLIKASI PIXELLAB DALAM PEMBUATAN PAMFLET PADA HIMPUNAN MAHASISWA BAHASA INDONESIA UNIVERSITAS MUHAMMADIYAH BONE - Herisman; Andi Srimularahmah; Muhammad Asdar (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Abstrak This study discusses the implementation of the Pixellab application in creating pamphlets for the Indonesian Language Student Association (HIMABINA) at Muhammadiyah University of Bone. The background of this research arises from the organization’s need for a practical and accessible publication medium capable of producing attractive and informative pamphlet designs. The purpose of this study is to analyze the use of Pixellab in pamphlet creation and to identify the supporting and inhibiting factors in its implementation. This research applies a descriptive qualitative method with data collected through interviews, observations, documentation, and questionnaires. The respondents consist of ten active HIMABINA members who are directly involved in designing organizational pamphlets. The data were analyzed using a thematic approach to identify patterns and meanings from respondents’ experiences. The results show that the implementation of Pixellab goes through four stages: downloading, introduction and socialization, independent exploration, and practical application in pamphlet creation. The application is considered helpful because of its simple interface, Android-based system, and flexibility. Frequently used features include text editing, layers, shapes, 3D text, and background removal. Most respondents expressed satisfaction since the app enhances creativity and basic graphic design skills. However, some challenges include limited features for complex designs, small phone screens, and paid premium features. In conclusion, Pixellab is effective as a design medium for student organization pamphlets and is recommended for continued use with basic design training support.